Lessons to be learned from top-50 global container port terminals efficiencies: A multi-period DEA-tobit approach - Nikolaou, Paraskevas; Dimitriou, Loukas (My University, 2021)
The growing competition among container port terminals enhances the pressure for optimizing their efficiency level in the performance of containers’ service. Comparing container terminals based on their performance is a complicated task due to the variety of ports’ type, scale, and service configuration. This however is an important task in the efforts of improving not only national trade transportation but also the global trade system, since valuable best practices can be identified and adopted among container terminals. Notwithstanding, available information about container port terminals’ efficiency level, based on their performance measured by the service of Twenty-foot Equivalent Units (TEUs), is yet incomplete due to the lack of information about which factors influence their efficiency the most. This additional information will support the decision-making processes of container terminals’ authorities to direct their focus on specific factors that will improve their efficiency. This paper investigates the efficiency of the top-50 global container port terminals that service the global freight supply chain in a period of 5 years (2013-2017) through a two-step procedure. First, a benchmarking analysis, namely, Data Envelopment Analysis, is implemented to estimate the efficiency level of the container port terminals. The second step involves the methodology followed in this paper which is further expanded to quantify the effects that different factors have on container terminals efficiency through the implementation of suitable Tobit regression models. The findings of this paper identify the benchmark container terminals that should be taken as examples for under-performing container port terminals and also points out the factors that must be enhanced for improving global trade system, like, number of cranes, terminal space and quay lenght.
Keywords: Container Port Terminals; Data Envelopment Analysis; Benchmark Analysis; Tobit Regression Model